Bis(thiocarbamates): Synthesis and Substituent Effects on the Barrier to N‐CO Rotation. Issue 6 (3rd June 2015) - Maouati, Hamida; Sanhoury, M. A. K.; Merlet, D.; Chehidi, I.
ABSTRACT: The synthesis of a new series of variously substituted bis(thiocarbamates) from the addition of dithiols to isocyanates is described. These bis(thiocarbamates) were fully characterized by NMR, IR, and HRMS analyses. In addition, the effect of different substituents on the hindered rotation about the N‐CO bond in these bis‐thiocarbamates was investigated through dynamic NMR experiments.